The impact of (K.W.L) strategy on developing students' critical thinking Department of Art Education with Artistic Appreciation (Journal of the College of Basic Education, 2023)
Summary of the research:The current research dealt with identifying the impact of the (K.W.L) strategy in developing critical thinking among students of the Department of Art Education in Artistic Appreciation, and the research community consisted of first-stage students, whose number was (197) students, and the researcher chose a sample for her research in a random manner, as they numbered (90) students They were divided into two groups (experimental and control). In her study, the researcher relied on the experimental design with partial control to achieve the goal of her research, to verify the validity and reliability of the experimental design for the research. Achievement test and post critical thinking test in favor of the experimental group.Keywords: (K.W.L) strategy, critical thinking, artistic appreciation